A survey and preparation of the local database on "Samut Songkhram 3 water cities" for preparing a local education curriculum of the Samut Songkhram Primary Educational Service Area Office - Phondee, Samran; Chesamae, Anhawi; Yamchuti, Urairat (Academic and Research Journal of Liberal Arts (Online), 2021)
This research Has the purpose to study, explore, analyze, and compile a database of local knowledge including geography, Social landscape, history, identity, wisdom and cultural way of people in Samut Songkhram Province. To support the preparation of local education courses of the Samut Songkhram Primary Educational Service Area Office by 0uality research using a survey research model collect information both from documents coupled with field studies the data were analyzed, synthesized, and the results were presented in descriptive analysis. The results showed that Samut Songkhram province's important knowledge of local knowledge that should be used as a database for developing local education courses for youth in the area can be divided into 5 issues: 1) Geography and social landscape Samut Songkhram Province is located in an area that is abundant downstream. It emerged as a uni0ue feature of the area, known as the "3 water cities" are fresh water, brackish water, salt water. 2) Local history It is an old town with continuous historical development. 3) Local identity that is clear, both the natural and cultural identity. 4) Wisdom That are diverse, especially with regards to lifestyle. And 5) Cultural heritage found that there are both tangible and intangible cultures such knowledge is valuable, meaningful and a key element in developing local sustainability through a learning process with local curriculum, education for local youths to build awareness of local value and importance. This learning will bring social power that can drive the transformation to the strength of the local community in the future.